Viral Release Threshold in the Salivary Gland of Leafhopper Vector Mediates the Intermittent Transmission of Rice Dwarf Virus - Chen, Qian; Liu, Yuyan; Long, Zhirun; Yang, Hengsong; Wei, Taiyun (Frontiers in Microbiology, 2021)
Numerous piercing-sucking insects can persistently transmit viral pathogens in combination with saliva to plant phloem in an intermittent pattern. Insect vectors maintain viruliferous for life. However, the reason why insect vectors discontinuously transmit the virus remains unclear. Rice dwarf virus (RDV), a plant reovirus, was found to replicate and assemble the progeny virions in salivary gland cell of the leafhopper vector. We observed that the RDV virions moved into saliva-stored cavities in the salivary glands of leafhopper vectors via an exocytosis-like mechanism, facilitating the viral horizontal transmission to plant hosts during the feeding of leafhoppers. Interestingly, the levels of viral accumulation in the salivary glands of leafhoppers during the transmitting period were significantly lower than those of viruliferous individuals during the intermittent period. A putative viral release threshold, which was close to 1.79 × 104 copies/ng RNA was proposed from the viral titers in the salivary glands of 52 leafhoppers during the intermittent period. Thus, the viral release threshold was hypothesized to mediate the intermittent release of RDV from the salivary gland cells of leafhoppers. We anticipate that viral release threshold-mediated intermittent transmission by insect vectors is the conserved strategy for the epidemic and persistence of vector-borne viruses in nature.